Combined U–Th/He and 40Ar/39Ar geochronology of post-shield lavas from the Mauna Kea and Kohala volcanoes, Hawaii - Aciego, S.; Jourdan, Fred; DePaolo, D.; Kennedy, B. (Pergamon-Elsevier Science Ltd, 2010)
Late Quaternary, post-shield lavas from the Mauna Kea and Kohala volcanoes on the Big Island of Hawaii have been dated using the 40Ar/39Ar and U–Th/He methods. The objective of the study is to compare the recently demonstrated U–Th/He age method, which uses basaltic olivine phenocrysts, with 40Ar/39Ar ages measured on groundmass from the same samples. As a corollary, the age data also increase the precision of the chronology of volcanism on the Big Island. For the U–Th/He ages, U, Th and He concentrations and isotopes were measured to account for U-series disequilibrium and initial He. Single analyses U–Th/He ages for Hamakua lavas from Mauna Kea are 87 ± 40 to 119 ± 23 ka (2σ uncertainties), which are in general equal to or younger than 40Ar/39Ar ages. Basalt from the Polulu sequence on Kohala gives a U–Th/He age of 354 ± 54 ka and a 40Ar/39Ar age of 450 ± 40 ka. All of the U–Th/He ages, and all but one spurious 40Ar/39Ar ages conform to the previously proposed stratigraphy and published 14C and K–Ar ages.The ages also compare favorably to U–Th whole rock–olivine ages calculated from 238U–230Th disequilibria. The U–Th/He and 40Ar/39Ar results agree best where there is a relatively large amount of radiogenic 40Ar (>10%), and where the 40Ar/36Ar intercept calculated from the Ar isochron diagram is close to the atmospheric value. In two cases, it is not clear why U–Th/He and 40Ar/39Ar ages do not agree within uncertainty. U–Th/He and 40Ar/39Ar results diverge the most on a low-K transitional tholeiitic basalt with abundant olivine. For the most alkalic basalts with negligible olivine phenocrysts, U–Th/He ages were unattainable while 40Ar/39Ar results provide good precision even on ages as low as 19 ± 4 ka. Hence, the strengths and weaknesses of the U–Th/He and 40Ar/39Ar methods are complimentary for basalts with ages of order 100–500 ka.